Globalization and Defunct Democracy in Arvind Adiga’s The White Tiger (Pursuits: A Journal of English Studies, 2025)
The paper examines how Arvind Adiga in The White Tiger brings forth the challenges of democracy as a judicious system of governance in the era of globalization. Charting an utterly dark immoral journey of the protagonist from stark poverty to prosperity, Adiga exposes the paralyzed democratic governance in its failure to guarantee fair distribution of wealth and resources. With a light-hearted tone, Adiga pleads for 21st century democracy that can outsmart the detrimental effects that globalization has instigated. The paper primarily employs close reading of the text for its primary data bringing scholars and thinkers on democracy and globalization with critics on Adiga and the text in question as secondary data.